I’jāzu al-Saj’i fī Sūrataī al-Nāzi’āt wa ‘Abasa - Faiz Utrujjatun Zahro (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
The purpose of this study was to determine the forms and types of poems in the verses of An-Naziat and ‘Abasa Surah in the Qur’an. Both of the Surahs were revealed in Mecca. While the An-Naziat is the 79th Surah and consists of 46 verses, the ‘Abasa is the 80th Surah and consists of 42 verses. This qualitative descriptive study used words or sentences containing poetic forms and types in An-Naziat and ‘Abasa Surah as the data. The results of the study showed that there were 30 data in the form of poetry; 12 of them were saja’ mutawazi, 17 of them were saja’ mutharaf, and one of them were saja’ muroso. Then, it could be concluded that there was a form of similarity in the end of the word or sentence (rhyme) and the division of poetry types in An-Naziat and Abasa. Finally, this study suggests that the next studies should analyze the beauty of the language in the Qur'an more specific.